UZBEKISTAN'S POTENTIAL IN THE BUILDING MATERIALS MARKET - Abduganiyeva , Sitorabonu (Innovatsion texnologiyalar, 2023)
This article aimed at highlighting the prospects and strategies for the development of the role of imports in the construction materials market of Uzbekistan, covers such problematic issues as Uzbekistan's competence in the production of construction materials, the rational use of local raw materials in the production of import-substituting construction materials, and the introduction of modern technologies in the production of construction materials.